Nuclear and particle physics - Walet, Niels (The University of Manchester, 2013)
This Web page provides a comprehensive set of lecture notes for the old physics course P615: Nuclear and Particle Physics at the former University of Manchester Institute of Science and Technology (UMIST). Written by Niels Walet (now at The University of Manchester) the notes cover the history of particle physics, particle accelerators and detectors, nuclear masses, the shell, collective and quark models, nuclear vibrations and reactions, Feynman diagrams and symmetries of strong force.